Geographic Access to High-Volume Care Providers and Survival in Patients with Bone Sarcomas: Nationwide Patterns in the United States. (17th August 2022) - Fujiwara, Tomohiro; Ogura, Koichi; Alaqeel, Motaz; Healey, John H.
Abstract : Background: Clinical practice guidelines recommend centralized care for patients with bone sarcoma. However, the relationship between the distance that patients travel to obtain care, institutional treatment volume, and survival is unknown. Methods: We used the National Cancer Database to examine associations between travel distance and survival among 8, 432 patients with bone sarcoma diagnosed from 2004 to 2015. Associations were identified using multivariable Cox regression analyses that controlled for sociodemographic, clinical, and hospital-level factors; subgroup analyses stratified patients by histological diagnosis, tumor stage, and pediatric or adult status. Results: Mortality risk was lower among patients who traveled ≥50 miles (≥80.5 km) than among patients who traveled ≤10 miles (≤16.1 km) (hazard ratio [HR], 0.69 [95% confidence interval (CI), 0.63 to 0.76]). Among hospital-level factors, facility volume independently affected survival: mortality risk was lower among patients at high-volume facilities (≥20 cases per year) than at low-volume facilities (≤5 cases per year), with an HR of 0.72 (95% CI, 0.66 to 0.80). The proportion of patients who received care at high-volume facilities varied by distance traveled (p < 0.001); it was highest among patients who traveled ≥50 miles (53%) and lower among those who traveled 11 to 49 miles (17.7 to 78.9 km) (32%) or ≤10 miles (18%). Patients who traveled ≥50 miles to a high-volume facility had a lower risk of mortality (HR, 0.65 [95% CI, 0.56 to 0.77]) than those who traveled ≤10 miles to a low-volume facility. In subgroup analyses, this association was evident among patients with all 3 major histological subtypes; those with stage-I, II, and IV tumors; and adults. Conclusions: This national study showed that greater travel burden was associated with higher survival rates in adults, a finding attributable to patients traveling to receive care at high-volume facilities. Despite the burdens associated with travel, modification of referral pathways to specialized centers may improve survival for patients with bone sarcoma. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.